Correlation Between Initial Endotracheal Tube Cuff Pressure, Rate of Pressure Rising and Postoperative Throat Symptom when Using Nitrous Oxide - Subsoontorn, Pattika; Saetia, Sirikwan (Thai Journal of Anesthesiology, 2022)
Background: Inappropriate endotracheal cuff pressure inflation can result in post operative sore throat. Even with appropriate initial cuff pressure, nitrous oxide may increase the pressure. Objective: To assess the initial cuff pressure in routine pilot balloon inflation technique, rate of the pressure rising and correlation between cuff overpressure and throat symptom when using nitrous oxide. Method: One hundred and fifty patients scheduled for surgery under general anesthesia with expected surgical time more than 120 minutes were included. After endotracheal intubation, the cuff pressure was recorded at 0, 15th, 30th, 45th, 60th, 90th, 120th minute then every hour until extubation during 50% nitrous oxide administration. Postoperative sore throat and hoarseness were assessed at 1 hour and at 24 hours after extubation. The duration of operation and pilot balloon inflation technique were also recorded. Result: The initial pressures were within 20-30 cmH2O in 52.6% of patients. The incidence of intraoperative overpressure episode was 73.3%. The average rate of pressure rising was 3.9 cmH2O/h (IQR 0.6-12 cmH2O/h). The incidence rate of postoperative throat symptom was 48.6%. The duration of intubation more than 180 minutes (adjusted relative risk 4.8; CI 2.1-10.6, P<0.001) and any episode of overpressure (adjusted relative risk 7.3; CI 2.5-21.1, P<0.001) were the important factors that increase risk. Conclusion: With routine pilot balloon inflation, a high incidence of endotracheal tube cuff overpressure is occurred in most patients undergoing general anesthesia by using nitrous oxide. Intubation duration and episode of overpressure were the two important risk factors.